The educational program effectiveness based on generative learning in the literary achievement of fourth-grade female students in the sociology subject - Hasan, Zainab Kadhum Abdul; Abed, Nedhal Issa (PT. Antis International Publisher, 2024)
The goal of the current research is to identify the effectiveness of an educational program based on generative learning in the achievement of fourth-grade female students in the subject of sociology. The two researchers used the experimental research method to achieve the research goal, the research sample consisted of two groups (experimental and control), each group consisting of (30) female students. The two researchers built a research tool to test achievement in sociology, it consisted of (50) multiple-choice items and essay questions. The results showed the superiority of the experimental group that studied using the educational program over the control group that studied using the usual method. The two researchers reached a set of recommendations and proposals through the research results